Motivation and retrospective appraisal of psychedelic study participation: a qualitative study in healthy volunteers - Laura Ley; Matthias E. Liechti; Anna M. Becker; Isabelle Straumann; Aaron Klaiber; Friederike Holze; Severin B. Vogt; Denis Arikci; Yasmin Schmid (Psychopharmacology, 2025)
Rationale Little is known about motives of healthy volunteers to participate in psychedelic trials and how they appraise their study experience retrospectively. Objectives This paper explored reasons why healthy people register for psychedelic trials, factors that they considered to contribute to either positive or negative study experiences, and under which circumstances they would seek a psychedelic experience again. Methods This study used the data of 151 healthy volunteers who had ingested serotonergic psychedelics in one of six randomized, double-blind, placebo-controlled crossover trials at the same research site under similar conditions. The data were analyzed through qualitative content analysis. Results The predominant motivations to participate in a trial were interest in psychedelics and an appealing setting. Expectations involved personal development and the occurrence of typical psychedelic effects. Hopes included transformative processes. The setting factors that promoted a positive experience were music and access to nature, whereas the sterile hospital environment was considered bothersome. Most participants valued the trusting relationship with their investigator. The most commonly criticized investigator characteristics were a perceived lack of support and investigator-induced psychological discomfort. Most participants considered their expectations exceeded and would take the study substances again, preferably in a setting in nature with friends. Conclusions This paper identified four pivotal factors to be considered for psychedelic study experiences: (1) a secure interpersonal relationship, (2) an aesthetically pleasing environment, (3) access to nature, and (4) the use of music. This analysis reveals subjective views of volunteers in psychedelic Phase-I trials and may improve research standards.